The Influence of Information Technology Mastery and Work Motivation on the Teacher Performance - Nisak, Khoirotun; Ratumanan, Tanwey Gerson; Rahabav, Patris (Institut Agama Islam Negeri Imam Bonjol Padang, 2023)
The aims of this research is to determine the effect of information technology mastery and work motivation on teacher performance. This research was conducted at SMA Negeri 6 Seram Bagian Timur and SMA Negeri 9 Seram Timur, involving 41 teachers. The results of this research explained that the data description for the variable mastery of information technology, obtained as many as 12 teachers (29.27%) had very high mastery of information technology, 25 teachers (60.98%) had high mastery of information technology and 4 teachers (9.75%) has moderate mastery of information technology. The description of the data for the work motivation variable in this research was that 16 teachers (39.02%) had very high work motivation, 16 teachers (39.02%) had high work motivation, and as many as 9 teachers (21.96%) had work motivation. In the middle category. Furthermore, for the teacher performance, it was found that 13 teachers (31.71%) had very high teacher performance, 22 teachers (53.66%) had high teacher performance, and 6 teachers (14.63%) had moderate performance. Based on the results of the analysis of the three hypotheses, the following conclusions can be obtained: (1) The mastery of information technology has no positive and significant influence on the teacher’s performance due to some factors; (2) There is a significant effect of work motivation on teacher performance. This is evidenced by Fcount = 27.750 Ftable = 3.24 with a coefficient of determination (R Square) of 0.416; (3) There is a significant influence of information technology mastery and work motivation together on the teacher’s performance. This is evidenced from Fcount = 15.650 Ftable = 3.24 with a coefficient of determination (R Square) value is 0.452